Amelioration of mangosteen micro propagation through leaf and seed segments (Garcinia Mangostana L.) - Sirchi, Mohammad Hossein Torabi; Abdul Kadir, Mihdzar; Abdul Aziz, Maheran; Abdul Rashid, Azmi; Rafat, Arash; Javadi, Mohammad Bagher (Academic Journals, 2008)
A micro-propagation system was developed for mangosteen (Garcinia Mangostana L.) using leaf sections and mature seeds. This study investigated the effect of various modified Murashige and Skoog (MS) medium supplemented with 6-benzylaminopurin (BAP) alone or in combination with α-naphthalene acetic acid (NAA) on multiple shoot induction from leaf and half seed explants. Among the treatments, leaf explants on medium supplemented with 2.0 mgL־¹ (w/v) of BAP gave the highest percentage of shoot formation (70.07%), highest number of shoots formed per explant (46.5%) and showed high mean shoot height (0.48 cm). It was observed that medium with 0.5 mgL־¹ NAA, did not induce shoot organogenesis, but induced callus in 90% of the leaf explants. Seed explantsgave the highest percentage of shoot formation (60.2%) and mean number of shoots per explant (9.5) on medium supplemented with 20 mgL־¹ (w/v) BAP and 10 mgL־¹ (w/v) NAA. However, highest mean shoot height (0.69 cm) was observed on medium supplemented with 10 mgL־¹ (w/v) BAP and 10 mgL־¹ (w/v) NAA. Callus induction from seeds was also observed in most of the treatments. Medium-supplemented 20 mgL־¹ (w/v) NAA gave the highest percentage of callus formation (83.36%). Subsequently, roots were induced from the shoots by pretreating these shoots in various indol-3-butyric acid (IBA) and NAA concentrations in various MS salt strengths. Root formation was obtained on one-quarter strength MS salt medium supplemented with 0.1 mg/L NAA (90.4%). Plantlets were acclimatized on media composed of soil + sand+ organic matter+ vermiculite (2: 2: 1: 1) with 80% survival.